Programa Aprender Mais: uma análise avaliativa da contribuição na melhoria da aprendizagem de alunos dos anos iniciais do ensino fundamental - Silva, Idelzulene Pereira Barros da (2024)
This research aims to investigate aspects of the Aprendir Mais program in the city of Fortaleza, which aims to strengthen the learning of all students in Portuguese and mathematics in elementary school, replacing the Federal Mais Educação Program, presenting the same purposes, of school reinforcement from a perspective full-time. Specifically, the research will focus on the 1st and 2nd year classes of a school unit in Fortaleza. To develop this research, the following question is raised: what is the contribution of the Learn More Program to improving the quality and strengthening of teaching? From this, the general objective is to analyze the Learn More Program and the pedagogical practices presupposed in its constitution from a teaching perspective. It is based on the areas of public educational policies with emphasis on the initial grades of education, thus being a multidisciplinary research. Methodologically, it is characterized as an applied research, with a qualitative and descriptive approach, regarding the objectives, these will be operationalized with data collection through a questionnaire with fifteen closed and open questions with the monitors and teachers of the mentioned classes. The results indicate that the Program presents itself as a great tool for contributing to the quality of teaching, however greater interest is needed from participants in maintaining its vitality. It is concluded that this research is important as it can bring a critical analysis to possible modifications and changes in educational policies in Ceará.